Analysis of genomic methylation level using micellar electrokinetic chromatography with UV detection. Issue 15 (9th July 2013) - Ferrone, Alessio; Pesce, Mirko; Franceschelli, Sara; Speranza, Lorenza; De Lutiis, Maria Anna; Grilli, Alfredo; Felaco, Mario; Patruno, Antonia
<x xml:space="preserve">Abstract</x> Analytical methods for quantification of 5′‐methylcytosine in genomes are important tools to investigate epigenetic changes in gene expression during development, differentiation, aging, or cancer. Here, we report a novel genomic methylation content assay based on enzymatic hydrolysis of DNA and MEKC separation of 5′‐deoxyribonucleoside monophosphates (dNMP) using the cationic surfactant CTAB as pseudostationary phase. Calf Thymus DNA was used during method development to determine electrophoretic parameters and electrolyte composition for a complete separation between 2′‐deoxycytosine‐5′‐monophosphate and 2′‐deoxy‐5′‐methylcytosine 5′‐monophosphate (d5mCMP). Methylated and not methylated oligonucleotides were used to confirm the identity of each peak and evaluate analytical parameters of the method. The LOD of the method was found to be 12.5 pmol/μL for d5mCMP.